A newly isolated chytrid fungus specialized in parasitizing heterocysts of the filamentous cyanobacterium Dolichospermum sp. - Xu, Xujian; Kasada, Minoru; Grossart, Hans-Peter; Ibelings, Bas W.; Van den Wyngaert; Silke (Springer Science and Business Media LLC, 2026)
Chytridiomycota (chytrids) are aquatic fungal parasites characterized by a stage of free-swimming zoospores and that are known to infect many phytoplankton species, typically killing the host cell. We report a novel chytrid species strictly infecting heterocysts of the N2-fixing cyanobacterium Dolichospermum sp. During a two-month Lake Stechlin (Germany) sampling campaign, two Dolichospermum morphotypes coexisted: coiled (dominant, chytrid infection found mainly on vegetative cells) and straight (rare, heterocysts targeted by the new chytrid). Phylogenetic and morphological analyses place this parasite into the phylum Chytridiomycota, order Lobulomycetales where it represents a novel lineage within a clade that includes uncultured parasites of algae and heliozoa. This is the first discovery of a cyanobacteria parasite within the order. Heterocyst-specific infection suggests a potential disruption of cyanobacterial N2-fixation. By creating a conditionally relevant pathway between filamentous N2-fixing cyanobacteria and zooplankton via chytrid zoospores, the ‘trophic dead end’ of large cyanobacteria may be temporarily alleviated during periods of nitrogen limitation. Though chytrid infections have been shown to re-shape aquatic food web structure through the so-called mycoloop, our study points to a specific nitrogen pathway via infection of heterocysts, which connects N2-fixing cyanobacteria with the lake food web and thus is of potential importance for aquatic nitrogen cycling.